2008
DOI: 10.1136/thx.2007.086470
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and asthma: a systematic review

Abstract: Epidemiological studies first demonstrated the association between obesity and asthma and they have begun to provide additional evidence to support causality: a doseeffect relationship, consistency across studies (especially among women) and the correct temporal order (ie, obesity before asthma). To date, relatively few studies have addressed reversibility, an important but less frequently demonstrated epidemiological criterion of causality. Reversibility suggests that if excessive weight is a risk factor for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
123
3
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(138 citation statements)
references
References 63 publications
(73 reference statements)
5
123
3
7
Order By: Relevance
“…Combining our results with other studies demonstrating improvement in asthma measurements with weight loss may further support obesity management in overweight children with asthma, especially at younger ages. [51][52][53] In addition to outpatient weight loss programs, our study may support interventions (such as nutrition consultations or identification/treatment of obesity comorbidities) during hospitalization, an important capture point in patients with poor primary care follow-up. 54,55 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Combining our results with other studies demonstrating improvement in asthma measurements with weight loss may further support obesity management in overweight children with asthma, especially at younger ages. [51][52][53] In addition to outpatient weight loss programs, our study may support interventions (such as nutrition consultations or identification/treatment of obesity comorbidities) during hospitalization, an important capture point in patients with poor primary care follow-up. 54,55 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review performed by Eneli et al looking at the effects of weight loss and asthma outcomes showed an improvement in at least one asthma outcome after weight loss, in patients of various age, country of origin or gender [93]. However, further research remains to be conducted on the relationships between obesity and asthma and on the influence of weight loss on various clinical inflammatory and physiological parameters.…”
Section: Obesitymentioning
confidence: 99%
“…A causal relationship between obesity and asthma has been suggested from animal and human studies [88][89][90] and an improvement in asthma symptoms, control and medication needs has been observed after weight loss in the obese [89,[91][92][93].…”
Section: Obesitymentioning
confidence: 99%
“…Data in adults are encouraging. [147][148][149][150][151] However, no studies have been conducted in children determining the impact of weight loss on asthma. Of the adult studies, only a handful has focused on asthma as a primary outcome (Table 2).…”
Section: Weight Lossmentioning
confidence: 99%
“…The most commonly noted improvements following weight loss were subjective reporting of asthma symptoms, rescue medication use, and quality of life. 151 It may be important to note that surgical weight loss has yielded improvements in lung volumes and asthma symptoms, but has yet to show consistent improvement in asthma-specific outcomes such as airway reactivity or airflow obstruction. From the studies to date, it is difficult to decipher general improvements in cardiorespiratory health that typically follow weight loss from asthma-specific improvements.…”
Section: Weight Lossmentioning
confidence: 99%